Coping strategies and their associated factors among caregivers of patients with schizophrenia in Kuantan, Malaysia - Kamarulbahri, Tengku Mohd Saifuddin Tengku; Ariaratnam, Suthahar; Nikmat, Azlina Wati; Abdullah, Nik Nairan; Khing, Tan Lee (Frontiers in Psychiatry, 2022)
Background: Experiencing effective coping strategies among caregivers of patients with schizophrenia is extremely crucial for mental health; however, there are limited data on associated factors that contribute to coping strategies among them. This research aims to determine the coping strategies used and their association with the sociodemographic characteristics, social support, and psychological distress among the caregivers of patients with schizophrenia (COPZ). Methods: This is a cross-sectional study involving 331 caregivers of patients with schizophrenia who were attending an outpatient psychiatric clinic, recruited through convenience sampling. The socio-demographic data was acquired from the respondents. The instruments used were Brief-COPE, The Multidimensional Scale of Perceived Social Support (MSPSS), and The Kessler’s Psychological Distress (K10). Descriptive analysis was performed, followed by univariate analysis and multiple linear regression analyses. Results: Multivariable analysis showed that psychological distress was a significant independent predictor of problem-focused, emotion-focused, and dysfunctional coping strategies. Good social support contributed to the usage of problem-focused and emotion-focused coping strategies. Conclusion: Good social support and psychological distress have been shown to have an association with coping strategies. A further prospective study and qualitative research are needed in understanding how coping strategies can help caretakers of people with Schizophrenia in Malaysia to develop a more holistic treatment for the patient.